2005
DOI: 10.1086/427780
|View full text |Cite
|
Sign up to set email alerts
|

rDEN4Δ30, a Live Attenuated Dengue Virus Type 4 Vaccine Candidate, Is Safe, Immunogenic, and Highly Infectious in Healthy Adult Volunteers

Abstract: The rDEN4 Delta 30 vaccine is safe and induced an antibody response that was broadly neutralizing against genotypically diverse DEN-4 viruses. It is a promising vaccine candidate for inclusion in a tetravalent dengue vaccine formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 44 publications
(59 reference statements)
5
111
1
Order By: Relevance
“…The clinical reactogenicity observed in recipients of the LGT/DEN4 vaccine was less than that observed in recipients of a similar dose of a previously reported live attenuated dengue DEN4 vaccine [32]. Rash and neutropenia were observed in some recipients of the previously tested DEN4 vaccine candidate, but not in LGT/DEN4 vaccinees.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The clinical reactogenicity observed in recipients of the LGT/DEN4 vaccine was less than that observed in recipients of a similar dose of a previously reported live attenuated dengue DEN4 vaccine [32]. Rash and neutropenia were observed in some recipients of the previously tested DEN4 vaccine candidate, but not in LGT/DEN4 vaccinees.…”
Section: Discussioncontrasting
confidence: 57%
“…This interpretation is offered with the caveat that the replication of the wild-type DEN4 parent has not been evaluated directly in humans. However, LGT/DEN4 induced viremia much less frequently in healthy adult volunteers than that observed for live attenuated DEN4Δ30 vaccine candidate derived from the same DEN4 parent and administered at the same dose [32].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Because of the important role of neutralizing antibodies as surrogates of protection, the validation of neutralization tests is a priority 128 . Current approaches to vaccine development involve using live attenuated viruses, inactivated viruses, subunit vaccines, DNA vaccines, cloned engineered viruses and chimeric viruses using yellow fever vaccine and attenuated dengue viruses as backbones [129][130][131][132][133][134] . TABLE 1 summarizes the most advanced vaccine candidates.…”
Section: Vaccine Developmentmentioning
confidence: 99%
“…First, reverse genetics has been used to introduce an attenuating 30 nucleotide (nt) deletion (Δ30) mutation into the 3'-UTR of cDNA clones of each DENV serotype [16][17][18][19][20][21]. In initial studies, the rDEN4Δ30 vaccine candidate was found to be attenuated in rhesus monkeys and phase I/II clinical trials in humans have demonstrated that infection with vaccine virus results in low viremia, is strongly immunogenic, and exhibits minimal reactogenicity without serious adverse events [20,22]. Recently, the rDEN1Δ30 vaccine candidate, which was also attenuated in rhesus monkeys, has been found to share a similar set of properties in clinical trials as that observed for rDEN4Δ30: low viremia, strong immunogenicity, and minimal reactogenicity in 20 volunteers [21].…”
Section: Introductionmentioning
confidence: 99%